The Role of Health Behaviors in the Prevention and Management of Hypertension in Pregnancy: Current Guidelines and Perspectives - Makuch, Rafał; Chrościcka , Alicja; Gała, Kamil; Czajka, Andrzej; Lenard, Paweł; Kucharski, Adam; Michalska, Sara; Pilarski, Konrad; Dewicka, Martyna; Wawrzyniak, Alicja Maria (Quality in Sport, 2024)
Introduction and purpose Hypertensive disorders during pregnancy are related to a greater risk of both maternal, and fetal as well as neonatal morbidity and mortality. This literature review aims to synthesize the health-promoting behaviors in daily life like diet, body mass, exercises in the prevention and management of hypertension and possible complications. Gestational hypertension occurs after 20 weeks’ pregnancy and usually resolves after 6 weeks’ postpartum. Diagnosis of gestational hypertension appears at values >140/90 mmHg in pregnant women. It has to be confirmed in out-of-office BP measurements, and if it’s not possible by two separate medical appointments. According to current European guidelines, pharmacological therapy should be introduced in pregnant women with sustained elevated blood pressure ≥ 150/95 mmHg and at values >140/90 mmHg in pregnant women with gestational hypertension. Summarizing the current understanding of risk factors in hypertensive disorders during pregnancy seeks to enhance implementing positive health behaviors in prevention. Materials and methods The following review of studies was based on articles obtained from the PubMed and Google Scholar databases. Key search terms included gestational hypertension, pre-eclampsia, diet, physical activity, pharmacological treatment, obesity, prevention. Conclusion The literature review highlights the importance of BP measurements, diet restrictions, exercises of a low to moderate-intensity, pharmacological treatment during pregnancy as key factors in prevention of gestational hypertension. Greater awareness of hypertension in pregnancy encourages optimism for comprehensive research in the future.